“A STROLL DOWN MEMORY LANE”: A REVIEW OF MARKETING PRINCIPLES IN GHANAIAN THEATRE - Tetteyfio-Manu, Sylvia; Brako, Daniel Kofi; Asante, Evans (UI Scholars Hub, 2023)
Classical theatre marketing has been a phenomenon since the emergence of Greek theatre. This involved various means of selling theatre performances. Although marketing principles in theatre patronage are key in selling performances to a prospective audience, there is a dearth of research on it locally. Also, as observed, some theatre companies do not utilise these marketing principles in marketing their performances. Thus, they end up running at a loss and not satisfying the targeted audience members. To investigate this problem, this paper seeks to trace the evolution of theatre marketing from Ancient Greek to the present day. It also explores how marketing principles can be adopted and applied in theatre marketing in selling Ghanaian theatre. The paper adopts a qualitative framework and approach. The participants are selected using purposive and convenience sampling techniques. Data is gathered using semi-structured interviews and document study for analysis. From the analysis, findings indicate that some theatre companies in Ghana employed similar marketing strategies to sell their plays. This enable them to promote their performances through radio, print, television and social media proficiently. It also revealed that marketing principles adopted in theatre, play a major role in selling every performance to satisfy an audience and generate expected revenue.